SCHOOL PHYSICAL EDUCATION AND HEALTH: CLIPPINGS CONCEPTUAL (Fiep Bulletin - online, 2011)
Physical education is considered a profession, area of scientific knowledge and discipline of the school curriculum. In this article, the role of physical education and its place in collective health is questioned. To this end we conducted a literature review on the subject. The Physical Education follows the biomedical model, which in turn, considers the Cartesian paradigm as its guideline. This research had as main objective to survey the main concepts of Health as the content of physical education. This is a literature search. Through the study and researches in the area, we make a critique of the dominant thinking in the area, which guides the causal physical activity and health. We concluded that physical education should go beyond the individual and biological aspects of their practices and for a new direction from the collective.
Keywords: Physical Education; Health; School